2014
DOI: 10.1128/jcm.00467-14
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Galactomannan, Beta- d -Glucan, Aspergillus Lateral-Flow Device, Conventional Culture, and PCR Tests with Bronchoalveolar Lavage Fluid for Diagnosis of Invasive Pulmonary Aspergillosis

Abstract: Galactomannan detection in bronchoalveolar lavage (BAL) fluid samples (GM test) 0) and PCR resulted in 100% sensitivity (specificity for probable/proven IPA, 95 to 98%). The performance of conventional culture was limited by low sensitivity, while that of the BDG test was limited by low specificity. We evaluated established and novel diagnostic methods for IPA and found that the Aspergillus PCR, LFD, and GM tests were the most useful methods for diagnosing the disease by using BAL fluid samples. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
192
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(210 citation statements)
references
References 53 publications
11
192
3
1
Order By: Relevance
“…Some physicians tend to avoid or delay bronchoscopy because of the risk of bleeding in the setting of thrombocytopenia or because they consider the invasive procedure to be too strenuous for patients with wasting diseases. Our findings as well as data of other studies 26 support the concept of obtaining specimens from the direct site of infection, for example, BALF, and outweigh the risks of the procedure itself with the significant diagnostic gain. The combination of PCR and GM in BALF resulted in a further increase of combined sensitivity (with a DOR of 29.2) with specificity remaining >90%.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Some physicians tend to avoid or delay bronchoscopy because of the risk of bleeding in the setting of thrombocytopenia or because they consider the invasive procedure to be too strenuous for patients with wasting diseases. Our findings as well as data of other studies 26 support the concept of obtaining specimens from the direct site of infection, for example, BALF, and outweigh the risks of the procedure itself with the significant diagnostic gain. The combination of PCR and GM in BALF resulted in a further increase of combined sensitivity (with a DOR of 29.2) with specificity remaining >90%.…”
Section: Discussionsupporting
confidence: 75%
“…34 The present study expands this concept by adding a simultaneous molecular detection tool, that is, Aspergillus-specific PCR. There are other studies of diagnostic performance of GM, PCR, and the benefit of test combination 26,35 with the trend that performance of both tests is generally better in samples from the site of infection, that is, BALF, than in blood. Nevertheless, results vary widely and are hardly comparable among each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LFD is easily performed using native BALF and yields results in 15 minutes. In recent studies, the high potential of this new assay in BAL IPA detection was shown in hematological malignancy and solid-organ transplant (SOT) patients (26)(27)(28)(29)(30)(31). However, no data on the performance of the LFD test in nonneutropenic patients with underlying respiratory diseases have been published to date.…”
mentioning
confidence: 99%
“…1. A total of seven studies were included in our analysis (Held et al, 2013;Hoenigl et al, 2012Hoenigl et al, , 2014Prattes et al, 2014;Thornton, 2008;White et al, 2013;Willinger et al, 2014). The characteristics of the studies are shown in Table 1.…”
Section: Overall Analysismentioning
confidence: 99%